The Development Model of Customer Loyalty Through Service Quality and Customer Satisfaction (Study on Regular ULaMM Customers of PT. Permodalan Nasional Madani, Palembang Branch Office) - Darmawan Darmawan; Agus Salim (Dinasti Publisher, 2023)
The aims of this study was to analyze the effect of service quality on loyalty through regular ULaMM customer satisfaction at PT. Permodalan Nasional Madani, Palembang Branch Officel. The research method is a quantitative method with survey techniques, involving distributing questionnaires through an online platform to collect data from a sample of 115 respondents. The statistical test used in this study is the SmartPLS-based Structural Equation Modeling (SEM) analysis. The results showed that there was an effect of service quality on loyalty through customer satisfaction and customer satisfaction could mediate the effect of service quality on loyalty. The better the service quality, the higher the customer loyalty.